Modal analysis of the 63 Square Building in Seoul, South Korea and its impact of subsidence and soil-structure interactions (SSI) - Hong, William; Kang, Minjung; Lee, Jay; Na, Sunmin (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
We conduct vibration analyses of 63 Building in Seoul, South Korea, using modal analysis and finite element modeling. The building is modeled as a solid structure having the shape of the real structure and with total weight and stiffness consistent with those of the real building. To better understand the fundamental periods of vibration of this structure and the associated mode shapes, we also consider structures with simplified geometry and perform modal analyses of them.